2019
DOI: 10.3168/jds.2019-16692
|View full text |Cite
|
Sign up to set email alerts
|

Relationships among bedding materials, bedding bacteria counts, udder hygiene, milk quality, and udder health in US dairy herds

Abstract: Bedding is an important source of teat end exposure to environmental mastitis pathogens. To better control environmental mastitis, we need an improved understanding of the relationships among bedding selection and management, bedding bacteria counts (BBC), and udder health (UH). The objectives of this crosssectional observational study were (1) to describe BBC, bedding characteristics, udder hygiene scores, bulk tank milk (BTM) quality, and UH in US dairy herds using 1 of 4 bedding materials; (2) describe the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
70
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(85 citation statements)
references
References 26 publications
(55 reference statements)
11
70
4
Order By: Relevance
“…Therefore, Krömker et al [ 40 ] published benchmarks for bacterial counts in unused bedding, indicating a reduced risk for cows to develop mastitis: For esculin-positive streptococci and coliforms: 10 4 cfu/g and for total bacteria counts: 10 6 cfu/g (sawdust) or 7 × 10 8 cfu/g (straw). In a recently published study, achievable benchmarks for used bedding were published: For streptococci-like organisms (SSLO): 5 × 10 5 cfu/cm 3 and for coliforms: 10 4 cfu/cm 3 [ 25 ]. Data from previous studies dealing with bacterial growth in bedding materials indicated a nonlinear relationship between time and bacterial counts but a maximum increase within 24 to 36 h of use following contamination of animals and feces [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, Krömker et al [ 40 ] published benchmarks for bacterial counts in unused bedding, indicating a reduced risk for cows to develop mastitis: For esculin-positive streptococci and coliforms: 10 4 cfu/g and for total bacteria counts: 10 6 cfu/g (sawdust) or 7 × 10 8 cfu/g (straw). In a recently published study, achievable benchmarks for used bedding were published: For streptococci-like organisms (SSLO): 5 × 10 5 cfu/cm 3 and for coliforms: 10 4 cfu/cm 3 [ 25 ]. Data from previous studies dealing with bacterial growth in bedding materials indicated a nonlinear relationship between time and bacterial counts but a maximum increase within 24 to 36 h of use following contamination of animals and feces [ 38 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cow pats were avoided at sampling to achieve an undistorted bedding sample. The number of days since fresh bedding had been most recently added to the pen were recorded [25].…”
Section: Bedding Samplesmentioning
confidence: 99%
“…Due to the high risk of bacterial load on animals, additional processing steps were included in the technology aimed at reducing the number of pathogens in the final product by increasing the temperature [27]. Further studies established that liquid-solid manure separation and thermal treatment of solids made the application of this technology possible in wetter and colder regions [11,[28][29][30]. Drying in a dryer drum 27.5 -27.5…”
Section: International Experiencementioning
confidence: 99%
“…Besides this, the RMS research is generally done on commercial farms (e.g. Rowbotham and Ruegg 2015, Bradley et al 2018, Patel et al 2019 where experiments are not controlled and also other housing conditions and management practices may affect the outcome. Thus, the aim of our study was to compare RMS bedding to peat bedding in a controlled cross-over experiment in a freestall barn with mattress stalls.…”
Section: Manuscript Received June 2020mentioning
confidence: 99%
“…Several studies and reports present no connection between used RMS bedding and increased somatic cell count (SCC) or mastitis incidence (Harrison et al 2008, Rowbotham and Ruegg 2016b, Bradley et al 2018). On the other hand, Rowbotham and Ruegg (2015) reported a higher degree of nonfunctioning mammary glands and discarded milk, and Patel et al (2019) reported poorer udder health indicators, on farms using RMS as a bedding material, which may indicate more challenges managing udder health on these farms. The review of Leach et al (2015) demonstrated no systematic connection between RMS bedding and a high SCC or incidence of clinical mastitis.…”
Section: Introductionmentioning
confidence: 99%